2004
DOI: 10.1111/j.1398-9995.2004.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine‐regulated accumulation of eosinophils in inflammatory disease

Abstract: The role of cytokines in the accumulation of eosinophil granulocytes in inflamed tissue has been studied extensively during recent years, and these molecules have been found to participate throughout the whole process of eosinophil recruitment. Haematopoietic cytokines such as IL‐3, IL‐5 and GM‐CSF stimulate the proliferation and differentiation of eosinophils in the bone marrow, and the release of mature eosinophils from the bone marrow into the blood is probably promoted by IL‐5. Priming of eosinophils in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
237
0
30

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(277 citation statements)
references
References 141 publications
10
237
0
30
Order By: Relevance
“…TNF-α is also an important chemoattractant for the recruitment of eosinophils into the lungs [30] and is a potent modulator of the immune and inflammatory responses. Inflammatory cells contribute to the generation of Th2 cytokines (IL-4, IL-5, and IL-13), chemokines (eotaxin and RANTES), and TNF-α, whose levels increase in the asthmatic lung [31].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is also an important chemoattractant for the recruitment of eosinophils into the lungs [30] and is a potent modulator of the immune and inflammatory responses. Inflammatory cells contribute to the generation of Th2 cytokines (IL-4, IL-5, and IL-13), chemokines (eotaxin and RANTES), and TNF-α, whose levels increase in the asthmatic lung [31].…”
Section: Discussionmentioning
confidence: 99%
“…The eosinophil number in BAL was not reduced by AG1478 treatment although this inhibitor significantly reduced the eotaxin expression in BAL supernatant, suggesting that airway eosinophilia in this rat model of acute asthma is not eotaxindependent. The recruitment of eosinophils may be mediated by many different mediators including RANTES, IL-5, IL-8 and leukotriene B4 [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of eosinophils may be mediated by many different mediators including RANTES, IL-5, IL-8 and leukotriene B4 [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CD4 + T cells polarized toward a Th2 type phenotype secrete cytokines (e.g. IL-4 and IL-5) which serve as potent eosinophil chemoattractants (Lampinen et al 2004). As a result, eosinophils constitute a prominent cell type observed during a Th2 type response and the presence of an eosinophil infiltrate at the site of inflammation is one of the most frequently used indicators for the development of such an immune response.…”
Section: Discussionmentioning
confidence: 99%